Impact of the national health insurance coverage policy on mecapegfilgrastim utilization for chemoradiotherapy-induced neutropenia in cancer patients in China: a retrospective real-world analysis - Fang, Wenqing; He, Jizhong; Wang, Ying; Zhu, Yulei; Qian, Xiaodan; Su, Dan; Gong, Jinhong; Shang, Jingjing; He, Yuan; Wu, Hong; Li, Xin (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate mecapegfilgrastim utilization for the prophylaxis of chemotherapy-induced neutropenia in cancer patients and to assess changes caused by the National Health Insurance Coverage (NHIC) policy.MethodsIndividual patient data, including demographics, medical insurance status, cancer type, and tumor stage, were extracted from electronic medical records in an oncology specialty tertiary hospital in Jiangsu Province, China. An interrupted time series (ITS) analysis with a segmented regression model was applied to evaluate the NHIC policy’s effects, and multivariate binary logistic regression analysis was used to identify key factors influencing mecapegfilgrastim utilization.ResultsThe proportion of cancer patients receiving mecapegfilgrastim increased from 8.17% before the NHIC policy implementation to 36.05% after its implementation (P < 0.001). Utilization rose abruptly following the policy intervention (β = 0.143, P < 0.001) and continued to increase significantly afterward (β = 0.011, P = 0.004). However, inequities were observed in mecapegfilgrastim usage among patient subgroups, with utilization closely associated with patients’ location, cancer type, and tumor stage after the policy implementation.ConclusionThe NHIC policy significantly increased mecapegfilgrastim utilization, enabling more cancer patients to access this medication and effectively benefiting them. To address persistent inequities, the government should consider introducing additional measures, such as increasing the insurance reimbursement cap and separating the cost of expensive innovative anticancer medicines from hospital medical insurance budgets.